Regional Government Policy Analysis against Coaching and Development of Physical and Physical Education Teacher for Junior High School in West Sumbawa Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The purpose of this study was to analyze local government policies on the development and development of sports and health physical education teachers in West Sumbawa Regency. This study uses a qualitative approach. The methods used are interviews, observations, and documentation. The subjects of this study were government agencies including Commission I DPRD, Department of Youth and Sports Education and Chairperson of MGMP Physical education Junior High School. Data is analyzed by triangulating data. The results of this study indicate that the local government policy on coaching and development of sports physical and health education teachers for Junior High School in West Sumbawa regency is seen in terms of policy program activities in improving teacher coaching and development in the form of activity programs contained in the Management Official Decree West Sumbawa Regency Regional Finance Number 23 of 2017